Musculoskeletal evaluation in severe haemophilia A patients from Latin America. (January 2014) - Ozelo, M. C.; Villaça, P. R.; Pérez‐Bianco, R.; Candela, M.; Garcia‐Chavez, J.; Moreno‐Rodriguez, B.; Rodrigues, M. B.; Rodriguez‐Grecco, I.; Solano, M. H.; Chumpitaz, G.; Morales‐Gana, M. M.; Ruiz‐Sáez, A.
Summary There is a paucity of literature on haemophilia treatment in Latin American countries, a region characterized by rapidly improving systems of care, but with substantial disparities in treatment between countries. The aim of this study was to evaluate the musculoskeletal status of haemophilia patients from Latin America and to examine the relationship between musculoskeletal status and treatment practices across countries. The Committee of Latin America on the Therapeutics of Inhibitor Groups conducted a survey of its member country representatives on key aspects of haemophilia treatment in 10 countries. Musculoskeletal status of patients was obtained during routine comprehensive evaluations between March 2009 and March 2011. Eligible patients had severe haemophilia A (factor VIII <1%) without inhibitors (<0.6 BU mL−1) and were ≥5 years of age. Musculoskeletal status was compared between three groups of countries, based primarily on differences in the availability of long‐term prophylaxis. Overall, 143 patients (5–66 years of age) were enrolled from nine countries. In countries where long‐term prophylaxis had been available for at least 10 years (Group A), patients aged 5–10 years had significantly better mean World Federation of Hemophilia clinical scores, fewer target joints and fewer affected joints than patients from countries where long‐term prophylaxis has been available for about 5 years (Group B) or was not available (Group C). In Latin America, the musculoskeletal status of patients with severe haemophilia without inhibitors has improved significantly in association with the provision of long‐term prophylaxis. As more countries in Latin America institute this practice, further improvements are anticipated.